Hashimoto’s thyroiditis is not a risk factor for thyroid cancer (Universa Medicina, 2018)
BackgroundThyroid carcinoma is the most common endocrine malignancy. Chronic inflammation can be involved in tumorigenesis. It is estimated that more than 20% of all tumors are caused by persistent inflammatory conditions. The objective of the present study was to compare the inflammatory factor level of erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and thyroiditis between benign and malignant thyroid nodules.MethodsA cross-sectional study was conducted involving 94 patients (47 patients with benign tumors as controls and 47 patients with malignant tumors as cases). ESR and CRP were measured and analyzed. Mean ESR and CRP in both groups was compared using independent t-test. The chi-square test was used to assess the risk of cancer in patients with Hashimoto’s thyroidits and with significance level at p